Islamic Character in Science Learning for Madrasah Ibtidaiyah Students in the 4.0 Industrial Revolution Era - Haqiqi, Arghob Khofya; Albar, Wakhid Fitri (Proceeding International Conference on Science and Engineering, 2019)
This study aimed to analyze and describe the development of science learning characterized by Islam for students of Islamic elementary schools in the era of the fourth industrial revolution. The existence of technological developments today leads to changes in social development. This certainly also has an impact on the character development of children, especially those at the elementary school or Islamic elementary school level. Science learning is one of learning in Islamic elementary schools, which is not only required to follow the development of these technologies but also cannot be separated from the Islamic character as a characteristic of madrasah. The research method used was literacy studies by collecting existing data from journal studies, books and other sources relevant to the problem. From the results of the study, it was found that science learning at the level of Islamic elementary schools must be in Islamic character and should follow the development of the present and existing technology. It is suggested to improve the curriculum and the science teachers’ ways of teaching based on the current technology.